Teachers’ self-efficacy in the implementation of inclusive education: Literature review - ika febrian kristiana (Journal of Educational, Health and Community Psychology, 2018)
Self-efficacy of teachers is a teacher's belief in self-competence that can be demonstrated in a given situation. Self-efficacy teachers have been extensively researched including in the context of inclusive education involving students with special needs. This study aims to conduct a literature review of the predictors and consequences of teacher self-efficacy in the setting of inclusive education involving S. Search literature using online database include ERIC, ProQuest, and Science Direct. The keywords used in the search was ("SEN" OR "inclusion) AND (" antecedent "OR" consequence ") AND" teacher self-efficacy. A total of 33 articles (N = 3472) were reviewed through a series of screening steps based on established inclusion and exclusion criteria. The findings show that the teacher's self-efficacy predictors come from internal (e.g. knowledge, personality profiles, experience interacting with disabled people, teaching experience, an experience of training) or external or situational (e.g. school climate). Teacher self-efficacy can have an impact on attitudes and behaviors on inclusion, work attitude (e.g. burnout, job satisfaction), collective self-efficacy, and student-related decision making (referral bias). There are contradictory research findings of and limited research on the impact of teacher self-efficacy on the development or achievement of students with special needs into findings that also become suggestions for further research, especially in Indonesia.Keywords: teachers’ self-efficacy, inclusion, Special Educational Needs (SEN), and review